Role of Dietary Metabolites in Regulating the Host Immune Response in Gastrointestinal Disease - El-Zaatari, Mohamad; Kao, John Y. (Frontiers in Immunology, 2017)
The host immune response to gastrointestinal (GI) infections, hypersensitivity reactions or GI cancers comprises numerous pathways that elicit responses on different host cells. Some of these include 1) the stimulation of mast cells via their IgE receptor, 2) the production of antibodies leading to antibody-mediated cytotoxic T / Natural Killer cell killing, 3) the activation of the complement pathway, and 4) the activation of the adaptive immune response via antigen presenting cell, T cell, and B cell interactions. Within the plethora of these different responses, several host immune cells represent major key players such as those of myeloid lineage (including neutrophils, macrophages, myeloid-derived suppressor cells) or lymphoid lineage (including T and B cells). In this review we focus on newly identified metabolites and metabolite receptors that are expressed by either myeloid or lymphoid lineages. Irrespective of their source, these metabolites can in certain instances elicit responses on a wide range of cell types. The myeloid-expressed metabolic enzymes and receptors we will discuss in this review include arginase 2 (Arg2), indoleamine-2,3-dioxygenase 1 (IDO1), hydroxycarboxylic acid receptor 2 (Hcar2; also called GPR109A), and immunoresponsive gene 1 (Irg1). We will also review the role of the lymphoid-expressed metabolite receptor that binds to the sphingosine-1-phosphate (S1P) sphingolipid. Moreover, we will describe the synthesis and metabolism of retinoic acid, and its effect on T cell activation. The review will then discuss the function of these metabolites in the context of GI disease. The review provides evidence that metabolic pathways operate in a disease- and context-dependent manner – either independently or concomitantly – in the GI tract. Therefore, an integrated approach and combinatorial analyses are necessary to devise new therapeutic strategies that can synergistically improve prognoses.